Analysis of Bird Diversity and Birdwatching Tracks as Education Tourism in Ngesrepbalong Village, Mount Ungaran - Desyakawa Huril'in; Tamara Lu'lu Dian Afifa; Selawati Nur Wahidah; Annisa Dwi Lestari; Margareta Rahayuningsih (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2025)
Education tourism is a sustainable activity aimed at reducing environmental impact, protecting ecosystems, promoting economic development, and improving the quality of life of local residents. Edutourism and recreation has important role in socio-economic development and environmental infrastructure. Ngesrepbalong Village is a rural area in Limbangan District, Kendal Regency, Central Java. The diversity of vegetation and the vastness of nature make this area an ideal habitat for various fauna, especially birds. Birdwatching is an edutourism activity that accordance with the potential of this village. Several areas show high potential to be utilized as birdwatching tracks. The research was conducted using the Index Point of Abundance (IPA) method, and the data were analyzed using the Shannon-Wiener Diversity Index and Simpson’s Evenness Index. Based on observations of the tracks in Ngesrepbalong Village, the bird diversity index values from highest to lowest were: Watu Ondo (3.03), Curug (2.80), Gempol (2.62), and Tea plantation (2.09), with an average value of 2.635. These results indicate a medium level of bird species diversity. Therefore, Ngesrepbalong Village has potential to be developed into an ideal destination for birdwatching and edutourism, offering natural beauty and biodiversity supported by a rich variety of vegetation.